“CABRI 3D SOFTWARE” TECHNOLOGY: STUDENTS’ PROBLEM SOLVING SKILLS WITH PROBLEM BASED INSTRUCTION MODEL APPROACH - Almira Amir; Ihamuddin Ihamuddin (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
Abstract Nowadays, 21st-century learning requires students to develop higher-order thinking skills, one of which is the ability to solve a problem. The purpose of this study was to analyze the effect of using the Problem Based Instruction model with the help of Cabri 3D Software on students' problem-solving skills. The method used in this research is an experimental method with a quantitative approach. While the design in this study used a pretest-posttest control group design, using an instrument in the form of a test. The target subjects in this study were students of class VIII MTs Muhammadiyah - 8 Siabu. Meanwhile, the data analysis technique used is inferential statistics in the form of a t-test. The results showed that the calculation of the t-test obtained t count = 2,708 and continued by looking at the table based on the sample size of 48 people, (the experimental class consisted of 23 people while the control class consisted of 25 people) at a significant level of 5% found t table = 2,012 then t count (2.708) > t table (2.012), it means that t is in the reception area. So it can be concluded that there is a significant effect of the Problem Based Instruction model with the help of Cabri 3D software on students' problem-solving abilities on the subject of spatial construction. The research implication is that the application of technology is needed to design innovative and credible thinking and student experiences in responding to the challenges of the 21st century, especially in problem-solving skills. Keywords: Cabri 3D Software, Problem-based instruction model, Problem-solving skills. Abstrak Dewasa ini, pembelajaran abad 21 menuntut siswa dalam untuk mengembangkan kemampuan dalam berpikir tingkat tinggi salah satunya seperti kemampuan dalam memecahkan sebuah masalah. Tujuan dari penelitian ini untuk menganalisis pengaruh penggunaan model Problem Based Instruction berbantuan Software Cabri 3D terhadap kemampuan pemecahan masalah siswa. Metode yang digunakan dalam penelitian ini adalah metode eksperimen dengan pendekatan kuantitatif. Sementara desain dalam penelitian ini menggunakan pretest-posttest control group design, dengan menggunakan instrumen berupa tes. Sasaran subyek pada penelitian ini merupakan siswa kelas VIII MTs Muhammadiyah - 8 Siabu. Adapun, teknik analisis data yang digunakan adalah statistik inferensial berupa uji-t. Hasil penelitian menunjukkan bahwa perhitungan uji-t yang diperoleh thitung = 2,708 dan dilanjutkan dengan melihat pada tabel berdasarkan jumlah sampel 48 orang, (kelas eksperimen terdiri 23 orang sedangkan kelas kontrol terdiri 25 orang) pada taraf signifikannya 5% ditemukan t tabel = 2,012 maka t hitung (2,708) > t tabel  (2,012), artinya t berada di daerah penerimaan. Sehingga dapat disimpulkan adanya pengaruh signifikan model Problem Based Instruction berbantuan Software Cabri 3D terhadap kemampuan pemecahan masalah siswa pada pokok bahasan bangun ruang. Implikasi penelitian yakni penerapan teknologi dibutuhkan untuk mendesain pemikiran dan pengalaman siswa yang inovatif dan berkredibel dalam menjawab tantangan abad 21 ini khususnya dalam keterampilan pemecahan masalah.Kata kunci: Keterampilan memecahkan masalah, Model instruksi berbasis masalah, Software Cabri 3D